A Longitudinal Randomized Controlled Trial Protocol to Evaluate the Effects of Wuqinxi on Dynamic Functional Connectivity in Parkinson’s Disease Patients - Li, Yuting; Zhang, Lanlan; Wu, Yin; Zhang, Jian; Liu, Ke (Frontiers in Human Neuroscience, 2021)
Background: Parkinson's disease (PD) is a neurodegenerative movement disease that includes non-motor symptoms such as cognitive impairment. Long-term mind-body exercise has been shown to improve cognitive ability in PD patients, but the methods of assessment and intervention were inconsistent across studies. Wuqinxi is a mind-body exercise that is easy to learn, has few physical and cognitive demands, and is recommended for PD patients. Dynamic functional connectivity (DFC) has been associated with cognitive alterations in PD, but no studies have yet explored the effects of Wuqinxi on this association. The current protocol is designed to measure the effects of long-term Wuqinxi intervention on cognition in PD patients, and explore the underlying neural mechanisms through DFC. Methods: A long-term single-blind, randomized trial will be conducted. PD patients and age- and gender-matched healthy controls will be recruited; PD patients will be randomly assigned to either Wuqinxi or balance groups, and healthy controls will all receive health education. The Wuqinxi group will receive a 90-min session of Wuqinxi intervention three times a week for 24 weeks, while the balance group will receive balance exercise instruction on the same schedule. Primary outcomes will include assessment of cognitive domains and dynamic temporal characteristics of functional connectivity. Secondary outcomes will include severity of motor symptoms, mobility, balance, and emotional state. Assessments will be conducted at baseline, at the end of 24 weeks of intervention, and 12 weeks after interventions have ended. Discussion: This study will provide evidence to the effects of Wuqinxi exercise on cognitive improvements in PD from the perspective of DFC, and will contribute to the understanding of neural mechanisms underlying cognitive enhancement through Wuqinxi practice. Trial registration: The study was prospectively registered with the Chinese Clinical Trial Registry (ChiCTR2000038517) on 18th January 2021.